Children presenting with chronic cough are serious problem to the family and primary care physicians - Zeman, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2012)
Chronic cough in children is among the problems that lead to frequent consultations with a doctor. Chronic cough has been associated with a variety of illnesses, including asthma, gastroesophageal reflux disease, allergic rhinitis, postviralillness, bronchiectasis, and passive smoking. Aspiration of foreign material and presence of tumor should always be considered. In many cases, the etiology of chronic cough is clearly declared in a patient’s history or on physical examination findings. Isolated chronic cough in children is rarely asthma.